Tafsir in Indonesia: A Historical Review and Analysis of Munāsabah in Tafsir Al-Mishbah - Nur Kholisah; Putri Salsabila Azkya (Aslama: Journal of Islamic Studies, 2025)
The atomistic approach in Qur'ānic studies often separates verses from the context of their wholeness, thus risking a rigid partial understanding and obscuring the moral message of the sacred text. Responding to these methodological challenges, this study aims to analyse the operational function of munāsabah in Tafsir Al-Mishbah as the main hermeneutic tool to reconstruct the meaning of verses that appear incoherent. By applying qualitative literature method and descriptive analysis of historical and textual data, this study examines how the logic of inter-verse relationship is built in the frame of Nusantara tafsir. The analysis reveals that in the midst of the transformation of Indonesian tafsir towards adab al-ijtima'i style, M. Quraish Shihab succeeded in proving the harmony of the Qur'anic structure through a variety of relationship patterns in Q.S. Al-Isrā', namely mudhāddah (opposition), istitrād (further mention), and tafsīr (explanation). This study concludes that the application of munāsabah effectively overcomes the problem of fragmentation of meaning by binding separate verses into a unified structure, resulting in a systematic interpretation product and avoiding the rigidity of textual understanding.